Clinically compatible subject-specific dynamic parallel transmit pulse design for homogeneous fat saturation and water-excitation at 141657T: Proof-of-concept for 14165CEST MRI of the brain - Levy, Simon; Herrler, Jürgen; Liebert, Andrzej; Tkotz, Katharina; Fabian, Moritz; Eisen, Christian; Grodzki, David; Uder, Michael; Dörfler, Arnd; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the benefits and challenges of dynamic parallel transmit (pTx) pulses for fat saturation (FS) and water-excitation (WE), in the context of CEST MRI. Methods "Universal" k(T)-points (for FS) and spiral non-selective (for WE) trajectories were optimized offline for flip angle (FA) homogeneity. Routines to optimize the pulse shape online, based on the subject's fields maps, were implemented (target FA of 110 degrees/0 degrees for FS, 0 degrees/5 degrees for WE at fat/water frequencies). The pulses were inserted in a CEST sequence with a pTx readout. The different fat suppression schemes and their effects on CEST contrasts were compared in 12 volunteers at 7T. Results With a 25%-shorter pulse duration, pTx FS largely improved the FA homogeneity (root-mean-square-error (RMSE) = 12.3 degrees vs. 53.4 degrees with circularly-polarized mode, at the fat frequency). However, the spectral selectivity was degraded mainly in the cerebellum and close to the sinuses (RMSE = 5.8 degrees vs. 0.2 degrees at the water frequency). Similarly, pTx WE showed a trade-off between FA homogeneity and spectral selectivity compared to pTx non-selective pulses (RMSE = 0.9 degrees and 1.1 degrees at the fat and water frequencies, vs. 4.6 degrees and 0.5 degrees). In the brain, CEST metrics were reduced by up to 31.9% at -3.3 ppm with pTx FS, suggesting a mitigated lipid-induced bias. Conclusion This clinically compatible implementation of dynamic pTx pulses improved the fat suppression homogeneity at 7T taking into account the subject-specific B-0 heterogeneities online. This study highlights the lipid-induced biases on the CEST z-spectrum. The results are promising for body applications where B-0 heterogeneities and fat are more substantial.
CRIS-Team WoS Importer:2022-09-30